Research on Optimization of Ventilation Method in Mining Face: A Case Study of Huoerxinhe Coal Industry - Fan, Jiangchun (Scientific Journal of Technology, 2025)
This paper takes the No. 3 coal seam mining face of Shanxi Huoerxinhe Coal Industry Co., Ltd. as the research object. Aiming at the problems existing in the current double-"U" type ventilation method, by comparing and analyzing the advantages and disadvantages of the single-"U" type and "Y" type ventilation methods, and considering the requirements for achieving the standard of gas drainage in the mine, the necessity and feasibility of optimizing the ventilation method are proposed. The research results indicate that the "Y" type ventilation method has significant advantages in solving upper corner gas accumulation, improving ventilation efficiency, and saving coal resources, making it an ideal choice for optimizing the ventilation method of the mining face in Huoerxinhe Coal Industry. This paper elaborates in detail on the implementation steps and safeguard measures of the optimization scheme, providing a reference for the optimization of ventilation methods in similar mines.